EmPHasis-10 as a measure of health-related quality of life in pulmonary arterial hypertension: data from PHAR. Issue 2 (25th February 2021) - Borgese, Marissa; Badesch, David; Bull, Todd; Chakinala, Murali; DeMarco, Teresa; Feldman, Jeremy; Ford, H. James; Grinnan, Dan; Klinger, James R.; Bolivar, Lena; Shlobin, Oksana A.; Frantz, Robert P.; et al.
Introduction: While the performance of the emPHasis-10 (e10) score has been evaluated against limited patient characteristics within the United Kingdom, there is an unmet need for exploring the performance of the e10 score among pulmonary arterial hypertension (PAH) patients in the United States. Methods: Using the Pulmonary Hypertension Association Registry, we evaluated relationships between the e10 score and demographic, functional, haemodynamic and additional clinical characteristics at baseline and over time. Furthermore, we derived a minimally important difference (MID) estimate for the e10 score. Results: We analysed data from 565 PAH (75% female) adults aged mean±sd 55.6±16.0 years. At baseline, the e10 score had notable correlation with factors expected to impact quality of life in the general population, including age, education level, income, smoking status and body mass index. Clinically important parameters including 6-min walk distance and B-type natriuretic peptide (BNP)/N-terminal proBNP were also significantly associated with e10 score at baseline and over time. We generated a MID estimate for the e10 score of −6.0 points (range −5.0–−7.6 points). Conclusions: The e10 score was associated with demographic and clinical patient characteristics, suggesting that health-related quality of life in PAH is influenced by both social factors and indicators of disease severity. Future studies are needed to demonstrate the impact of the e10 score on clinical decision-making and its potential utility for assessing clinically important interventions. Understanding quality of life is critical given the profound impact PAH has on patient lives. This study shows that emPHasis-10 score correlates with demographic and clinical characteristics, and is potentially useful as a clinical trial end-point. https://bit.ly/3k57oaB